2010
DOI: 10.1007/s00441-010-1110-5
|View full text |Cite
|
Sign up to set email alerts
|

Localization of plasminogen in mouse hippocampus, cerebral cortex, and hypothalamus

Abstract: Although the tissue plasminogen activator/plasminogen system contributes to numerous brain functions, such as learning, memory, and anxiety behavior, little attention has as yet been given to the localization of plasminogen in the brain. We have investigated the localization of plasminogen in the adult mouse brain by using immunohistochemistry. In the hippocampus, plasminogen immunoreactivity was seen in the pyramidal cell layer as numerous punctate structures in neuronal somata. An electron-microscopic study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…In line with this assumption, several studies have reported that the principal physiological plasmin inhibitor, the α2-antiplasmin, is highly expressed in rodent hippocampus [38], [39]. Besides, it has been shown that the t-PA substrate plasminogen is localized intracellularly, mainly in the neuronal somata of the CA3 and CA1 layers [40]. Overall data suggest that rt-PA-induced increase in hippocampal mature BDNF expression is a plasmin-independent mechanism.…”
Section: Discussionsupporting
confidence: 56%
“…In line with this assumption, several studies have reported that the principal physiological plasmin inhibitor, the α2-antiplasmin, is highly expressed in rodent hippocampus [38], [39]. Besides, it has been shown that the t-PA substrate plasminogen is localized intracellularly, mainly in the neuronal somata of the CA3 and CA1 layers [40]. Overall data suggest that rt-PA-induced increase in hippocampal mature BDNF expression is a plasmin-independent mechanism.…”
Section: Discussionsupporting
confidence: 56%
“…Currently, there is an ample body of literature regarding the involvement of Pg/ Pm system in CNS development, normal neural functioning as well as neurologic disorders [1,2,5]. Our data expand evidences that rat brain cells are able to produce Pg and are in accordance with the previous reports indicating that Pg is expressed by specific populations of hippocampal, cortical and hypothalamic neurons in murine brain [13,26]. Moreover, the available ultrastructural observations demonstrate the vesicular localization of Pg in brain neurons.…”
Section: Fig 2 Representative Fluorescence Micrographs Of Plasminogsupporting
confidence: 91%
“…In the previous papers, angiostatins are described as constantly formed by several types of retina-resident cells [10]. So far, studies of angiostatins in brain tissue have been limited, with few exceptions [11][12][13], to effects of angiostatin-encoding genetic engineering constructions, which are expressed in the models of rat and human glioma cells developed for testing anti-angiogenic strategy for malignant brain tumor therapy [14,15].…”
Section: The Purpose Of the Present Study Was To Examine The Plasminomentioning
confidence: 99%
“…The following primary antibodies were used in the experiments: mouse monoclonal IgG against Math1 (Clone rabbit polyclonal IgG against Iba1 (dilution 1:700; WAKO Pure Chemical Industries, Osaka, Japan), oligodendrocyte transcription factor 2 (Olig2; dilution 1:500; Millipore, Billerica, MA, USA), Sox2 (dilution 1:2000; Millipore), S100β (dilution 1:3200; Yanaihara Institute, Shizuoka, J a p a n ) , V E G F -A ( d i l u t i o n 1 : 2 0 0 ; S a n t a C r u z Biotechnology), and VEGF-C (dilution 1:100; Abcam); guinea pig IgG against GFAP (YN-2011; dilution 1:400; Nakano et al 2015) and microtubule-associated protein 2 (MAP2, NH-2004;dilution;Taniguchi et al 2011). For nuclear staining, sections were incubated with 4′,6-diamidino-2-phenylindole (DAPI; 1 μg/ml; Dojindo, Kumamoto, Japan).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%